Factors that Influence Mother’s Behavior in Fulfilling Toddler Nutrition at the Age of 12-36 Months - Rifzul Maulina; Mochammad Bagus Qomaruddin; Ardhiles Wahyu Kurniawan (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan, 2021)
Abstract Improper feeding practices are the initial cause of the occurrence of nutritional problems in infants and toddlers, if this condition occurs over time, long enough, and continuously it will have an impact on the child’s growth. This study aims to the factors that influence the mother's behavior in fulfilling toddler nutrition. The design of this research is a cross-sectional approach. The sample number in this study was 238 mothers of respondents who have children aged 1-3 years. The research location is in the work area of the Tajinan Health Center. Malang Regency, East Java. The independent variables in this study were perceived susceptibility, perceived severity, perceived usefulness, perceived barrier, cues to action, and self-efficacy. The dependent variable of the study is the behavior of mothers in providing nutrition. Samples were taken using random cluster sampling. Data was collected using a questionnaire. The data were analyzed by using the chi-square test with a significance level of <0.05. The results showed that perceived vulnerability (p = 0.297), perceived seriousness (p = 0.201), perceived benefits (p = 0.197), cues to act (p = 0.068) and self-efficacy (p = 0.205) there was no relationship between behavior mother. Only perceived barriers (p=0.028) had a relationship with the mother’s behavior. Health workers at the public health center can provide audio-visual interventions to improve the behavior of mothers in providing the nutritional needs of their children. Keywords: mother’s behavior, nutritional toddlers, theory of health belief model Abstrak Praktik pemberian makan yang tidak benar merupakan penyebab awal terjadinya masalah nutrisi pada bayi dan baduta yang apabila kondisi ini terjadi dalam waktu yang cukup lama dan terus menerus maka akan berdampak pada pertumbuhan anak. Tujuan penelitian ini adalah faktor yang mempengaruhi Ibu dalam pemenuhan kebutuhan nutrisi pada anak usia balita. Desain penelitian ini adalah cross sectional. Jumlah sampel dalam penelitian ini adalah 238 ibu responden yang memiliki anak usia 1-3 tahun. Lokasi penelitian di wilayah kerja Puskesmas Tajinan. Kabupaten Malang, Jawa Timur. Variabel independen dalam penelitian ini kerentanan yang dirasakan, keparahan yang dirasakan, manfaat yang dirasakan, persepsi penghalang, isyarat untuk bertindak dan efikasi diri. Variabel dependen penelitian adalah perilaku ibu dalam memberikan nutrisi. Sampel diambil dengan cara Cluster random sampling. Pengumpulan data menggunakan instrumen kuesioner terstruktur dengan kuesioner. Analisa data dengan uji chi square, level signifikan P value < 0,05. Hasil menunjukkan bahwa variabel-variabel : kerentanan yang dirasakan (p=0,297), keparahan yang dirasakan (p=0,201), manfaat yang dirasakan (p=0,197), isyarat untuk bertindak (p=0,068) dan efikasi diri (p=0,205) tidak ada hubungan antara perilaku ibu. Hanya hambatan yang dirasakan (p=0,028) berhubungan dengan perilaku ibu. Petugas kesehatan di Puskesmas harus memberikan intervensi secara audio visual untuk meningkatkan perilaku Ibu dalam pemenuhan kebutuhan nutrisi bagi anaknya. Kata kunci: perilaku ibu, nutrisi balita, teori health belief model